The Study’s Chemical Interaction of the Sodium Silicate Solution with Extender Pigments to Investigate High Heat Resistance Silicate Coating - Cuong Manh Le; Thu-Huong Le (Journal of Analytical Methods in Chemistry)
Silicate coating is water-based paint with many advantages and wide applications in many different industries. However, there are still some problems with silicate coating: how to increase its resistance to heat at high temperatures and prolong the life of the coating. Silicate paints have high durability and longevity dependent mainly on the chemical interaction of the silicate binder with extender pigments. Therefore, our groups have studied the geopolymerization process of the sodium silicate solution with extender pigments to investigate high heat resistance silicate coating. The effect of curing time on the chemical interaction between sodium silicate solution and extender pigments (ZnO, TiO2, Fe2O3, CaCO3, and Na2SiF6) was investigated by Fourier transform infrared spectroscopy (FT-IR), thermal gravimetric analysis (TGA), and X-ray diffraction (XRD). The shift of antisymmetric stretching vibration of the Si-O-Si bond (1060 cm−1) to low frequency and increase of the intensity of the Si-O-Si stretching as curing time increases from 1 to 20 days are due to the increased chemical interaction between extender pigments (ZnO, TiO2, Fe2O3, CaCO3, and Na2SiF6) and sodium silicate solution. Moreover, TG results of ZnO-silicate, TiO2-silicate, CaCO3-silicate, Na2SiF6-silicate, and Fe2O3-silicate coating at 1 and 20 days of curing show high residual geopolymer about 69–90% at 800°C. Thus, we proposed that the geopolymerization process between sodium silicate solution and extender pigments (ZnO, TiO2, Fe2O3, CaCO3, and Na2SiF6) increases when the curing time from 1 to 20 days leads to forming geopolymer silicate with high thermal stability. In addition, the optimal mixing ratio between sodium silicate solution and extender pigments (ZnO, TiO2, Fe2O3, CaCO3, and Na2SiF6) is as follows: 25% binder (sodium silicate solution), 8% ZnO; 5% TiO2, 5% Fe2O3, 1% Na2SiF6, 21% CaCO3, 34% H2O, and 1% additives to make high heat resistance silicate coating with temperature resistance at 1000°C.